2005
DOI: 10.1002/cncr.21424
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prescreening of papanicolaou smears

Abstract: Population stratification results from unequal, nonrandom genetic contribution of ancestors and should be reflected in the underlying genealogies. In Quebec, the distribution of Mendelian diseases points to local founder effects suggesting stratification of the contemporary French Canadian gene pool. Here we characterize the population structure through the analysis of the genetic contribution of 7,798 immigrant founders identified in the genealogies of 2,221 subjects partitioned in eight regions. In all but o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…RPS is a useful quality improvement technique in the gynecologic cytology laboratory [1,2,3,4,5,6,7,8,9,10,11]. As our data shows, missed cases detected by rapid pre-screening are associated with a significant number of CIN1 and CIN3 and higher lesions on histology.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…RPS is a useful quality improvement technique in the gynecologic cytology laboratory [1,2,3,4,5,6,7,8,9,10,11]. As our data shows, missed cases detected by rapid pre-screening are associated with a significant number of CIN1 and CIN3 and higher lesions on histology.…”
Section: Discussionmentioning
confidence: 51%
“…Rapid pre-screening (RPS) is a useful quality improvement technique that not only can estimate the sensitivity and specificity of both the laboratory and the individual cytotechnologists (CTs) in the laboratory in actual practice, but can detect errors before the final diagnosis and can thus improve the estimated sensitivity of the laboratory overall [1,2,3,4,5,6,7,8,9,10,11]. In addition, it has recently been shown that long-term use of RPS significantly improves the estimated sensitivity of a subset of individual CTs in routine screening, presumably by providing constant, accurate, real-time feedback, improving both the accuracy and precision of the laboratory [12].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, all the cases included in the current study relate to a routine screening population. The cases included in the study underwent RPS in a manner similar to that which we have previously reported[89] with the following modifications. The majority of screeners spend between 15 and 30 min to rapidly prescreen one set of approximately 20 slides each day, allowing 45–90 s to screen each slide.…”
Section: Methodsmentioning
confidence: 99%
“…Outro método que tem sido abordado com a finalidade de aumentar a sensibilidade do exame citopatológico é o pré-escrutínio rápido, que consiste no escrutínio rápido de todos os esfregaços, durante um tempo limitado de no máximo 120 segundos, antes do escrutínio de rotina. Assim como na revisão rápida, todos os esfregaços identificados como suspeitos e que não foram identificados pelo escrutínio de rotina são posteriormente submetidos a uma revisão detalhada por um profissional experiente, que determinará o diagnóstico final 25,27,54,58,65,[67][68][69] . A exemplo da revisão rápida, esse método tem sido praticado principalmente no Reino Unido.…”
Section: Pré-escrutínio Rápido De Todos Os Esfregaçosunclassified
“…A exemplo da revisão rápida, esse método tem sido praticado principalmente no Reino Unido. Duas vantagens do pré-escrutínio rápido em relação à revisão rápida são descritas: primeira, o trabalho fica mais interessante para os escrutinadores porque a prevalência das anormalidades é maior devido ao fato de que todos os esfregaços são submetidos à pré-avaliação, ao passo que, na revisão rápida pósescrutínio de rotina, os esfregaços anormais identificados são separados e somente os negativos são revisados; segunda, a sensibilidade relativa do pré-escrutínio rápido e do escrutínio de rotina pode ser estimada 29,46,54,62,65,67,69 .…”
Section: Pré-escrutínio Rápido De Todos Os Esfregaçosunclassified